2015
DOI: 10.5194/hess-19-3925-2015
|View full text |Cite
|
Sign up to set email alerts
|

Definition of efficient scarcity-based water pricing policies through stochastic programming

Abstract: Abstract. Finding ways to improve the efficiency in water usage is one of the most important challenges in integrated water resources management. One of the most promising solutions is the use of scarcity-based pricing policies. This contribution presents a procedure to design efficient pricing policies based on the opportunity cost of water at the basin scale. Time series of the marginal value of water are obtained using a stochastic hydro-economic model. Those series are then post-processed to define step pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However, the water price will fluctuate due to water shortages. The lack of a link between water price and water scarcity and the absence of incentives for water-saving behavior may weaken users' perception of water scarcity [72,73]. Therefore, a market-based water price response to water shortage should be involved in the model in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the water price will fluctuate due to water shortages. The lack of a link between water price and water scarcity and the absence of incentives for water-saving behavior may weaken users' perception of water scarcity [72,73]. Therefore, a market-based water price response to water shortage should be involved in the model in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…However, their water pricing strategies are not linked to the marginal benefit of water use. Macian-Sorribes et al [29] proposed an efficient annual pricing policy based on the marginal benefit of water resources at the basin scale. Its application in Mijares River basin showed that this pricing policy could generate an incentive for water conservation during the scarcity periods and increase the economic benefit in the basin.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From this approach, this adds an uncertainty component to the prediction because this fraction does not depend on time. The recorded value of target water year to assess the predictive reliability, 28.4 Hm³ was supplied by the Jucar River Basin Authority (please, see Reference [41]). On the other hand, the reliability of the predictive model is shown in Table 6, both a general approach and a detailed one developed through a definition of TNCR intervals which is an uninfluenced fraction of the time.…”
Section: Management Scenariosmentioning
confidence: 99%
“…From this approach, this adds an uncertainty component to the prediction because this fraction does not depend on time. The recorded value of target water year to assess the predictive reliability, 28.4 Hm 3 was supplied by the Jucar River Basin Authority (please, see Reference [41]).…”
Section: Management Scenariosmentioning
confidence: 99%
See 1 more Smart Citation